Inside Back Cover: Probing CO2 Reduction Pathways for Copper Catalysis Using an Ionic Liquid as a Chemical Trapping Agent (Angew. Chem. Int. Ed. 41/2020). Issue 41 (31st August 2020) - Zhang, Gui‐Rong; Straub, Sascha‐Dominic; Shen, Liu‐Liu; Hermans, Yannick; Schmatz, Patrick; Reichert, Andreas M.; Hofmann, Jan P.; Katsounaros, Ioannis; Etzold, Bastian J. M.
Abstract : Gaining a mechanistic understanding of electrocatalytic processes is usually a challenging task. In their Research Article on page 18095, B. J. M. Etzold and co‐workers propose a new facile way to probe the CO2 reduction pathways on copper by employing an ionic liquid as a chemical trapping agent, which alters the product spectrum by selectively suppressing the formation of ethylene, ethanol, and n‐propanol. Analyzing the altered product spectrum provides a unique way to disentangle complex reaction networks of CO2 reduction.